Experimental-Morphological Study of Several Types of Fibrillar Structured Drainages for Glaucoma Surgery - N. S. Khodjaev; M. N. Kolomeytsev; A. V. Sidorova; V. V. Molchanov; N. G. Sedush; T. H. Tenchurin (Oftalʹmologiâ)
Purpose: based on the results of an experimental study in vivo, to determine the optimal type of fibrillar structured drainages for glaucoma surgery.Material and methods. An experimental morphological study was performed on 32 rabbits of the chinchilla breed, which were divided into 4 groups of 8 animals each. The rabbits were implanted with fibrillar structured drains from polyurethane, polyethylene terephthalate, polyamide, polylactide. In the postoperative period, a postoperative inflammatory reaction was assessed. After removing the animals from the experiment, the eyes were subjected to morphological examination.Results. In rabbits with drainage from polyurethane, a mild congested hyperemia was noted in visual evaluation compared with the pair eye during the entire follow-up period. The eye reaction to the operation was regarded as a 1st degree. In more distant terms, there was a proliferation of subconjunctival tissue in the projection of the operation zone. In histological examination, the implant was represented by thin fibrous structures throughout the volume of drainage, a uniform distribution of macrophages, lymphocytes, among the fibers. In rabbits with drainage from polyethylene terephthalate, the reaction of the eyeball to the implantation of the polymeric material corresponded to the 0 degree. When a histological study was carried out along the periphery of the drainage, a thin capsule was formed. In rabbits with drainage from polyamide, the reaction of the eyeball corresponded to 1 degree. Histological examination showed that the fibrous structure of drainage was practically not determined, an abundance of cellular elements was observed throughout the drainage: macrophages and multinucleate giants predominated, fibroblasts, fibroblasts, lymphocytes, and newly formed connective tissue fibers between the drainage fibers were present. When analyzing the results obtained during the implantation of the matrix from the polylactide, the reaction of the eyeball corresponded to the 0 degree. Histological examination showed the preservation of fibrous structure of drainage, a moderate accumulation of macrophages was determined between the fibers, single giants, single lymphocytes were present.The conclusion. Fibrillar structured drains based on polylactide due to a stable highly porous structure, high biocompatibility and biodegradability create favorable conditions for transport of aqueous humor and formation of outflow pathways.